2016
DOI: 10.1002/asna.201512306
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up spectroscopic observations of HD 107148 B: A new white dwarf companion of an exoplanet host star

Abstract: We report on our follow‐up spectroscopy of HD 1071478 B, a recently detected faint co‐moving companion of the exoplanet host star HD 107148 A. The companion is separated from its primary star by about 35″ (or 1790 AU of projected separation) and its optical and near infrared photometry is consistent with a white dwarf, located at the distance of HD 107148 A. In order to confirm the white dwarf nature of the co‐moving companion, we obtained follow‐up spectroscopic observations of HD 107148 B with CAFOS at the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…detected in our surveys. This demonstrates the efficiency of these projects and shows that the multiplicity of the exoplanet host stars is significantly underestimated (see also Mugrauer &Dinçel 2016, andMugrauer et al 2014).…”
mentioning
confidence: 76%
“…detected in our surveys. This demonstrates the efficiency of these projects and shows that the multiplicity of the exoplanet host stars is significantly underestimated (see also Mugrauer &Dinçel 2016, andMugrauer et al 2014).…”
mentioning
confidence: 76%
“…Later, Mugrauer et al (2014) confirmed the WD companion as HD 107148 B (we continue to call the main sequence star HD 107148 without adding an extra "A"). For the WD companion Mugrauer & Dinçel (2016) obtained a mass of M W D = 0.56 ± 0.05 M , an effective temperature of T eff = 6150 ± 250 K, a cooling age of 2.1 ± 0.27 Gyr, a surface gravity of log g = 7.95 ± 0.09 cm s −2 and a luminosity of L = (2.0 ± 0.2) × 10 −4 L . By assuming the initial-tofinal-mass-relation for white dwarfs from Catalan et al (2008), Mugrauer & Dinçel (2016) derived a progenitor mass of 1.4 ± 0.6M , leading to an estimated total age of 6.0 ± 4.8 Gyr for the WD companion.…”
Section: Stellar Parametersmentioning
confidence: 99%
“…In the Chandra observation, the primary was detected, while Tidal star-planet interaction 23 the secondary was not. The secondary component is a white dwarf (Mugrauer & Dincel 2016). The angular separation between the components is ρ = 35.0 .…”
mentioning
confidence: 99%